PEEK interbody fusion cage with double-drug sequential delivery function as well as preparation method and application of PEEK interbody fusion cage
By forming a three-dimensional porous network structure and sustained-release intermediate layer on the PEEK intervertebral fusion device, combining the sequential release of BMP-2 and alendronate, the problem of disordered drug release in the prior art is solved, and the bone is significantly improved Integrate performance.
Patent Information
- Application Number
- CN202411382267.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
AI Technical Summary
The existing modified PEEK intervertebral fusion devices are difficult to meet the sequential release requirements in vivo in terms of drug release, which limits the further improvement of the osseous integration performance of the implant.
BMP is achieved by pretreating the surface of the polyether etherketone carrier, combining alendronate and dopamine to form a sustained-release intermediate layer, and loading bone morphogenetic proteins into the crosslinked hyaluronic acid gel layer to achieve BMP -2 and alendronate sodium release in sequence.
It significantly enhances osteogenic activity, promotes osteointegration, stimulates osteoblast proliferation and differentiation in the early stage, inhibits osteoclast activity in the middle and late stages, and significantly improves the fusion effect of bone implant materials.
Smart Images

Figure CN119257797A_ABST
Abstract
Description
Technical Field
[0001] The invention patent relates to the technical field of intervertebral fusion devices, in particular to a PEEK intervertebral fusion device with dual-drug sequential delivery and its preparation method and application. Background Art
[0002] Spinal fusion is a traditional spinal surgical procedure that is widely used to treat a variety of spinal diseases, including spondylolisthesis, lumbar spinal stenosis, degenerative disc disease (DDD), trauma, tumor reconstruction, and scoliosis. With the advancement of surgical techniques, the widespread use of intervertebral fixators (ICs), and improved living conditions, spinal fusion surgery has grown exponentially in the past few decades. Since Bagby first proposed the use of a hollow porous stainless steel intervertebral cage to treat cervical spondylotic myelopathy in 1988, this intervertebral cage (cage) fusion technology has rapidly gained prominence in human clinical practice and was approved by the U.S. Food and Drug Administration (FDA) for specific spinal diseases in 1996. In the decades since then, efforts have been made to improve the stability of implantable cages, reduce cage subsidence, and increase fusion rates. Cages can restore intervertebral height and improve intervertebral fusion rates compared to autologous bone implants.
[0003] Since the 20th century, polyetheretherketone (PEEK) cages have been considered superior to titanium cages and have become the mainstream choice due to their elastic modulus and radiolucency similar to cortical bone. However, the biological inertness of the PEEK surface limits the bone integration of implants. Therefore, combining modified PEEK with a multifunctional coating to improve the bone integration ability of PEEK implants would be an economically feasible solution.
[0004] Existing modified PPEK mostly achieves the effect of roughening and increasing the contact area through sulfonation, and can obtain a drug-loaded polyetheretherketone implant by adding drugs to the hydrogel and drying it, such as a new type of drug-loaded 3D printed polyetheretherketone implant and its preparation method disclosed in CN115382017B; or a metal or non-metallic coating is loaded on the surface of the material matrix through plasma spraying, spin coating, etc. The preparation process of the above coating is simple, but the loaded drug particles are mostly embedded in the coating or gel, which is difficult to meet the needs of sequential release in vivo, limiting the further improvement of the bone integration performance of the implant. Summary of the invention
[0005] The purpose of the present invention is to solve the existing technical problems, and a PEEK intervertebral fusion device for sequential dual-drug delivery is proposed. Sodium alendronate is fixed on the surface of a sulfonated polyetheretherketone carrier by polydopamine, and BMP-2 is loaded into the cross-linked hyaluronic acid gel layer, so that BMP-2 and alendronate are released sequentially from the intervertebral fusion device, showing a significant synergistic effect in osteogenic activity.
[0006] The present invention provides a PEEK intervertebral fusion device for sequential dual-drug delivery, comprising a polyetheretherketone carrier, a slow-release middle layer and an outer layer arranged from inside to outside;
[0007] The surface of the polyetheretherketone carrier is pretreated to form a three-dimensional porous network structure;
[0008] The sustained-release intermediate layer comprises sodium alendronate and dopamine, and sodium alendronate is synergistically coated on the surface of the polyetheretherketone carrier through self-polymerization of dopamine to form a sustained-release intermediate layer;
[0009] The outer layer includes a gel layer loaded with bone morphogenetic protein, and hyaluronic acid forms a gel layer on the surface of the sustained-release intermediate layer through a cross-linking reaction. The surface of the gel layer is evenly loaded with bone morphogenetic protein to achieve sequential delivery of bone morphogenetic protein and alendronate sodium.
[0010] Preferably, the pore size of the three-dimensional porous network structure is 1 to 4 μm.
[0011] The present invention provides a method for preparing a PEEK intervertebral fusion device for sequential dual-drug delivery, comprising the following steps:
[0012] 1) Pretreatment of polyetheretherketone carrier:
[0013] The polyetheretherketone is immersed in concentrated sulfuric acid to obtain a sulfonated polyetheretherketone sample; the sulfonated polyetheretherketone sample is rinsed with deionized water, immersed in a sodium hydroxide solution for 5 minutes, ultrasonically washed with deionized water again, and naturally dried to obtain a polyetheretherketone carrier with a three-dimensional porous network structure on the surface;
[0014] 2) Construction of sustained-release intermediate layer:
[0015] The alendronate sodium solution and the dopamine solution are mixed to obtain solution A; the polyetheretherketone carrier obtained in 1) is immersed in solution A and magnetically stirred overnight at 4° C. in the dark; then rinsed with deionized water to obtain an intervertebral fusion cage preparation covered with a sustained-release intermediate layer;
[0016] 3) Construction of the outer layer:
[0017] The intervertebral fusion device preparation obtained in 2) is placed in a sodium hyaluronate solution containing a cross-linking agent, and a gel layer is formed on the surface of the intervertebral fusion device preparation after reacting at 4°C for 8-12 hours, and the cross-linking agent residue is thoroughly rinsed off; after washing, the preparation is sterilized, and the polyetheretherketone carrier is immersed in a bone morphogenetic protein solution overnight under a sterile environment at room temperature, and the intervertebral fusion device is obtained after natural drying.
[0018] Preferably, the bone morphogenetic protein solution in 3) is a 25-30 μg / mL BMP-2 solution.
[0019] Furthermore, the concentration of the BMP-2 solution in 3) may be 5-100 μg / mL.
[0020] Preferably, in 2), the mass ratio of dopamine to sodium alendronate in solution A is 2:0.2-5.0, and the pH value of solution A is 8.0.
[0021] Furthermore, solution A in 2) is prepared by mixing 2 mg / mL dopamine solution and 1 mg / mL alendronate sodium solution.
[0022] Preferably, the cross-linking agent in 3) is an EDC / sNHS cross-linking agent, sNHS is N-hydroxysulfosuccinimide, the EDC concentration in the cross-linking agent is 10-100 mg / mL, and the sNHS concentration is 11 mg / mL.
[0023] Preferably, 1) the concentration of concentrated sulfuric acid is 95-98wt%, and the soaking time is 5-10min.
[0024] Preferably, the sterilization treatment in 3) is ultraviolet sterilization or irradiation sterilization for not less than 1 hour.
[0025] Preferably, the sodium hyaluronate concentration in the sodium hyaluronate solution in 3) is 3 mg / mL
[0026] Furthermore, the polyetheretherketone in 1) can be one or more of a plate and a hollow tube.
[0027] The application of the PEEK intervertebral fusion device with dual-drug sequential delivery provided by the present invention in the preparation of bone implant materials, because the slow-release middle layer and the outer layer have good degradation characteristics, BMP-2 can be delivered early and quickly continuously, accompanied by the gradual dissolution of ALN from the polyetheretherketone carrier, this administration method can stimulate osteoblast proliferation and differentiation in the early stage, and inhibit osteoclast activity in the middle and late stages, significantly enhance the synergistic effect between the two drugs, and promote bone integration. It meets the needs of bone implant material preparation such as stimulating the proliferation and differentiation of bone marrow mesenchymal stem cells, promoting the expression of osteogenesis-related genes ALP, RUNX-2, etc., hindering the differentiation and proliferation of osteoclasts, and promoting intervertebral bone integration.
[0028] The beneficial effects of the present invention are: through the intermediate sustained-release layer formed by dopamine and sodium alendronate, BMP-2 is loaded into the cross-linked gel layer, so that BMP-2 and sodium alendronate are released sequentially from the intervertebral fusion cage, showing a significant synergistic effect in terms of osteogenic activity;
[0029] The in vitro release results showed that the BMP-2 in the PEEK intervertebral fusion device showed an initial burst release on the first day, initially releasing about 30%, and then continuously and stably released most of the BMP-2 protein (85%) within the first week. Then, the release amount dropped sharply in the second week; and trace amounts could still be detected after four weeks. In contrast, ALN showed delayed release kinetics, releasing only about 3.7% in the first week; then, its release rate gradually accelerated, reaching a peak in the 5th week, and continued to release slowly for about 70 days. By sequentially delivering the released BMP-2 and alendronate, it can stimulate osteoblast proliferation and differentiation in the early stage, and inhibit osteoclast activity in the middle and late stages, significantly enhancing the synergistic effect between the two drugs and promoting bone integration. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The surface morphologies of different coatings on the surfaces of PEEK obtained in Example 1 and Comparative Example 1 and each group of samples after modification under a scanning electron microscope (white scale: 5 μm, 10 μm);
[0031] Figure 2 The difference in Fourier infrared characteristic spectra of PEEK obtained in Example 1 and Comparative Example 1 and each group of samples after modification thereof;
[0032] Figure 3 The release trend of BMP-2 and ALN of the BMP-ALN-SPEEK sample obtained in Example 1 in a PBS solution at 37°C;
[0033] Figure 4 The proliferation of bone marrow mesenchymal stem cells extracted from osteoporotic rats in Example 3 after being cultured on the surface of each group of samples for the 1st, 3rd and 7th days;
[0034] Figure 5 The F-actin staining images of the BMSCs morphology of each group of samples after 7 days of osteogenic induction in Example 3 (white scale: 100 μm);
[0035] Figure 6 The results of alkaline phosphatase activity and mineralized bone staining (Alizarin Red S) of bone marrow mesenchymal stem cells extracted from osteoporotic rats in Example 3 on the surface of each group of samples after induced differentiation into osteoblasts for 7 days, wherein ALP activity is standardized to total protein content (nmol / min / mg), and ARS quantification is expressed as the absorbance of the supernatant at a wavelength of 620nm;
[0036] Figure 7 The RUNX-2 immunofluorescence staining results of the surfaces of the samples of each group after 7 days of osteogenic induction in Example 3, wherein RUNX-2 was stained red and the cell nucleus was stained blue (white scale: 200 um);
[0037] Figure 8 The results are the quantitative detection results of tartrate-resistant acid phosphatase (TRAP) in the cell lysate after RAW264.7 cells were cultured on the surface of each group of samples for 7 days in Example 3, wherein the TRAP activity was standardized to the total protein content (nmol / min / mg).
[0038] Fig. 9 The results of the antibacterial performance of each group of samples against Staphylococcus aureus measured by the inhibition zone method in Example 4; Fig.10 These are three-dimensional reconstructed images of new bone formation in different groups of samples in the L4 / L5 posterolateral lumbar transverse process fusion rat model of Example 5 (white scale: 2 mm);.
[0039] Fig.11 The histological evaluation results of new bone formation in rats of each group in Example 5 8 weeks after L4-L5 posterolateral lumbar transverse process fusion surgery, wherein HE staining of decalcified bone tissue, black arrows: newly mineralized bone, blue arrows: newly formed blood vessels, white arrows: fibrous connective tissue;
[0040] Fig.12 These are the thermogravimetric analysis results of nanohydroxyapatite (HA), nanohydroxyapatite loaded with sodium alendronate and dopamine polymer (HA-ALN), and nanohydroxyapatite loaded with dopamine (PDA@HA) in Example 6. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0042] Example 1 Preparation of PEEK intervertebral fusion cage (BMP-2-ALN-SPEEK) for sequential delivery of dual drugs
[0043] 1) Pretreatment of polyetheretherketone carrier:
[0044] The polyetheretherketone (PEEK) sheet and hollow tube were cut by a puncher and a small cutter, respectively, to obtain a PEEK disc with a diameter of 1 cm and a hollow stent with an outer diameter of 5 mm, an inner diameter of 3 mm, and a length of 10 mm. Subsequently, acetone, ethanol, and deionized water were used for ultrasonic cleaning in sequence to obtain a PEEK sample.
[0045] At room temperature, the PEEK sample was immersed in 95-98w% concentrated sulfuric acid for 5 minutes to obtain a sulfonated polyetheretherketone sample; the sulfonated polyetheretherketone sample was rinsed with deionized water for 5 minutes and immersed in a 6wt% sodium hydroxide solution for 5 minutes. Finally, it was ultrasonically washed three times with deionized water at room temperature, each washing time was 5 minutes, and naturally dried to obtain a polyetheretherketone carrier (SPEEK sample) with a three-dimensional porous network structure on the surface.
[0046] 2) Construction of sustained-release intermediate layer
[0047] A 4 mg / mL alendronate sodium solution and a 2 mg / mL dopamine solution were mixed at a ratio of 1:1 to obtain a solution A; the SPEEK sample obtained in 1) was immersed in the solution A and magnetically stirred overnight in a refrigerator at 4°C in the dark; then, the sample was rinsed with deionized water for 5 times to obtain a PDA-ALN-SPEEK sample coated with PDA-ALN;
[0048] 3) Construction of the outer layer
[0049] The PDA-ALN-SPEEK sample was placed in a sodium hyaluronate solution containing EDC / sNHS crosslinker and placed in a 4°C refrigerator for reaction for 12 hours. The crosslinker concentrations were EDC50mg / mL and sNHS11mg / mL respectively; the sodium hyaluronate concentration in the sodium hyaluronate solution was 3mg / mL. After completion, it was thoroughly rinsed 5 times for 10 minutes to completely remove the crosslinker residue. After cleaning, the sample was placed in a clean bench for 1 hour of ultraviolet sterilization. The sample was then soaked in a BMP solution with a concentration of 25μg / mL overnight, and the PEEK intervertebral fusion device was obtained after natural drying. The PEEK intervertebral fusion device (PEEK disc / stent) was placed in a sterile glass culture dish and sealed with plastic wrap as a BMP-2-ALN-SPEEK sample.
[0050] Comparative Example 1 Preparation method of BMP-2-SPEEK scaffold
[0051] The difference from Example 1 is that after step 1), step 2) is omitted and the SPEEK sample is directly subjected to step 3) to obtain a BMP-2-SPEEK sample.
[0052] Combination Figure 1-2The morphologies of PEEK, SPEEK, ALN-SPEEK, BMP-2-SPEEK, and BMP-2-ALN-SPEEK were characterized by scanning electron microscopy and Fourier transform infrared spectroscopy (FTIR). After treatment with concentrated sulfuric acid, the surface roughness of SPEEK was significantly improved compared with the originally smooth PEEK, forming a high-density three-dimensional porous network structure. The size of these micropores is mostly between 1-4μm, and there are many protrusions on the surface of the micropores. Subsequently, the porous structure of the surface of ALN-SPEEK treated with polydopamine-alendronate (PDA-ALN) solution was covered with a dense dopamine layer, and the surface was adhered to small dendritic particles, indicating that ALN was successfully loaded on the surface of SPEEK with the help of PDA's strong adhesion properties and abundant modification sites. A dense gel-like hyaluronic acid layer was formed on the surface of BMP-2-SPEEK by the EDC / sNHS cross-linking method, which significantly enhanced the interaction between hyaluronic acid molecules, thereby achieving excellent mechanical properties. The surface morphology of BMP-2-ALN-SPEEK was similar to that of ALN-SPEEK, with a portion of biconcave disc-shaped BMP-2 protein evenly distributed outside the sodium hyaluronate layer.
[0053] Example 2 In vitro release of BMP-2-ALN-SPEEK
[0054] The BMP-2-ALN-SPEEK sample obtained in Example 1 was immersed in phosphate buffered saline (PBS) at 37°C to evaluate the long-term release behavior of BMP-2 and ALN. Figure 3 As shown, it is obvious that BMP-2 in the BMP-2-ALN-SPEEK sample showed an initial burst release on the first day, initially releasing about 30%, followed by a continuous and stable release of most of the BMP-2 protein (85%) within the first week. Then, the release amount dropped sharply in the second week; and trace amounts could still be detected after four weeks. In contrast, ALN showed delayed release kinetics, releasing only about 3.7% in the first week; then, its release rate gradually accelerated, reaching a peak in the 5th week, and continued to release slowly for about 70 days. Due to the good degradation characteristics of the dual-drug coating, BMP-2 was delivered early and rapidly continuously, accompanied by the gradual dissolution of ALN from the carrier. This mode of administration can stimulate osteoblast proliferation and differentiation in the early stage, and inhibit osteoclast activity in the middle and late stages, significantly enhancing the synergistic effect between the two drugs and promoting bone integration.
[0055] Example 3 Cell experiment of dual drug sequential delivery system
[0056] Osteogenesis induction: Bone marrow mesenchymal stem cells extracted from osteoporotic rats were inoculated and cultured on the surfaces of the five samples (PEEK, SPEEK, ALN-SPEEK, BMP-2-SPEEK, and BMP-2-ALN-SPEEK) of Example 1 and Comparative Example 1.
[0057] Figure 4 The cell proliferation was obtained by using the CCK-8 kit to detect the kit after the cells were cultured on the sample surface for 1, 3, and 7 days. The OD values detected in each group of samples increased with time, further indicating that each group of samples had almost no toxicity to the cells. In addition, it was observed that BMP-2-ALN-SPEEK did not show significant differences on the first day compared with the other four groups. On the third day, the CCK8 activity of BMP-2-SPEEK and BMP-2-ALN-SPEEK was higher than that of the other three groups, and on the seventh day, it was found that BMP-2-ALN-SPEEK significantly enhanced cell proliferation. The good biocompatibility of BMP-2-ALN-SPEEK further confirms its potential to enhance cell viability and promote cell proliferation. This enhancement can be attributed to the rough surface of SPEEK and the sustained and stable release of BMP-2 in the early stage, which effectively stimulated the proliferation and differentiation of bone marrow mesenchymal stem cells.
[0058] Figure 5 Immunofluorescence staining of each sample after 7 days of culture using F-actin and DAPI to detect the cytoskeleton, it can be observed that the cells cultured on BMP-2-ALN-SPEEK showed better morphological stability, specifically, bone marrow mesenchymal stem cells (BMSCs) appeared more stretched in BMP-2-ALN-SPEEK, and the structural integrity of the cytoskeleton was significantly improved. In addition, these cells showed significant cell-to-cell interactions by extending filopodia to each other and even forming connections.
[0059] The above results indicate that the dual-drug coated BMP-2-ALN-SPEEK has superior biocompatibility, which is manifested in stronger cell proliferation ability and more stretched cell morphology.
[0060] After 7 days of osteogenic induction, the marker enzymes alkaline phosphatase (ALP) and Alizarin Red S (ARS) were quantitatively examined for each sample group, where ALP activity was normalized to total protein content (nmol / min / mg), and ARS was quantified as the absorbance of the supernatant at a wavelength of 620 nm. Figure 6As shown in the figure, we found that ALP expression was more significant on SPEEK compared with smooth PEEK, indicating that its expression level was higher on SPEEK. This difference may be related to the roughness of the SPEEK surface, which provides more adhesion sites, which is conducive to cell attachment and growth. At the same time, significantly upregulated ALP expression was observed in both the BMP-2-SPEEK group and the ALN-SPEEK group, indicating that BMP-2 and ALN were successfully released from the sample surface and promoted the expression of osteogenesis-related genes, thereby enhancing the expression of ALP. However, in the BMP-2-ALN-SPEEK group, ALP activity was the most active, and the BMP-2 and ALN released successively from the surface showed a synergistic effect, making the osteogenesis effect of this group of samples the most significant. The expression trend of ARS was similar to that of ALP.
[0061] Immunofluorescence was used to evaluate the osteogenic activity of samples after 7 days of osteogenic induction. RUNX-2, as a key transcription factor required for osteoblast differentiation and chondrocyte maturation, plays an important role in the osteogenesis process. Previous studies have shown that BMP-2 and ALN can effectively increase the expression level of RUNX-2 and further promote osteoblast differentiation and mineralization. Figure 7 As shown, in the immunofluorescence staining experiment of RUNX-2, it was observed that both BMP-2 and ALN could significantly enhance the expression of RUNX-2, among which the expression of BMP-2-ALN-SPEEK protein was the strongest compared with the other four groups.
[0062] Mouse macrophage-like cell line RAW264.7 cells were inoculated and cultured on the surface of each sample of Example 1 and Comparative Example 1, and 50 ng / mL of nuclear factor κB receptor activator ligand (RANKL) was added to a complete medium containing M-CSF at a concentration of 30 ng / mL to induce differentiation into osteoclasts. After 7 days of continuous induction, the cells were lysed and stained using a TRAP staining kit, and TRAP activity was standardized to total protein content (nmol / min / mg). Figure 8 As shown, the PEEK group exhibited the most significant TRAP activity, followed by the SPEEK group and the BMP-2-SPEEK group, while the TRAP expression levels were almost undetectable in the ALN-SPEEK and BMP-2-ALN-SPEEK groups. The above results clearly demonstrated that the successful release of ALN effectively hindered the differentiation and proliferation of osteoclasts.
[0063] Example 4 Antibacterial performance of dual-drug sequential delivery system
[0064] The antibacterial properties of each group of samples against Staphylococcus aureus were determined by the inhibition zone method. Fig. 9 As shown, both BMP-2-ALN-SPEEK and ALN-SPEEK exhibited significant antibacterial activity.
[0065] Example 5 Effect of the dual-drug sequential delivery system on promoting spinal fusion in vivo under osteoporosis conditions
[0066] Through posterolateral lumbar transverse process fusion surgery, each sample of Example 1 and Comparative Example 1 was implanted into the posterolateral transverse process of L4-L5 of rats with osteoporosis caused by ovariectomy to construct a spinal fusion model corresponding to each group. Eight weeks after the operation, the spinal specimens containing the implanted stent samples were taken out and scanned using micro-CT. The images were processed with CTvox software, and visual two-dimensional and three-dimensional reconstructed images were constructed and quantitatively analyzed. Due to the radiotransmittance of PEEK, the stent cannot be displayed in the image. Therefore, bone regeneration is directly evaluated by observing the morphology of the transverse processes and evaluating the gap between the L4-5 transverse processes from the front and side. Fig.10 As shown in the figure, there was almost no new bone formation on the transverse process surface of the PEEK scaffold, the transverse process morphology was clear, and the transverse process gap was wide; the transverse process of the SPEEK scaffold was slightly widened, and the transverse process gap was reduced, indicating that new bone formation was limited; ALN-SPEEK and BMP-2-SPEEK scaffolds showed stronger bone regeneration activity compared with the above two groups, which was mainly manifested in the blurred boundaries of the transverse processes, especially in the BMP-2-SPEEK group, where the gaps between the transverse processes were difficult to distinguish; for rats implanted with BMP-2-ALN-SPEEK, the morphology of the L4 and L5 transverse processes completely disappeared, and the adjacent transverse processes were completely connected, indicating that the double-drug coated BMP-2-ALN-SPEEK scaffold induced successful L4 and L5 spinal fusion.
[0067] Furthermore, the cut lumbar fusion area was stained with hematoxylin-eosin (HE) 4 weeks after decalcification. Fig.11 As shown in the figure, the results are consistent with the trend of CT images. Only a small amount of newly mineralized bone formation was observed at the edge of the transverse process bone cortex in the PEEK scaffold; after successful loading of BMP-2 and ALN, the mineralized area of ALN-SPEEK, BMP-2-SPEEK and BMP-2-ALN-SPEEK sample groups was significantly expanded, and dense trabecular formation was observed in the BMP-2-ALN-SPEEK group. Although the thickness of the trabecular bone was still relatively thin, it showed the greatest degree of bone regeneration, confirming the complete healing of the L4-L5 vertebrae. This shows that the sequential release of BMP-2 and ALN maximizes the promotion of intervertebral bone integration.
[0068] Example 6 Loading capacity of dual-drug sequential delivery system
[0069] Nano-hydroxyapatite (HA) was used as a fixed carrier, and the fixed carrier was added to the mixed solution A, and magnetic stirring was carried out overnight at 4°C in the dark to obtain a HA-ALN sample. The concentration of dopamine in the mixed solution was 2 mg / mL, and the concentration of ALN was 1 mg / mL.
[0070] Nanohydroxyapatite (HA) was used as a fixed carrier, and the fixed carrier was added to a dopamine solution with a concentration of 2 mg / mL, and magnetic stirring was carried out at 4°C in the dark overnight to obtain a PDA@HA sample.
[0071] Fig.12 Thermogravimetric analysis structures of nano-hydroxyapatite particles before and after loading alendronate sodium and dopamine (HA-ALN) and dopamine (PDA@HA). The results show that in the coating formed on the surface of the hydroxyapatite carrier by the mixed solution, the loading mass ratio of dopamine to ALN is approximately 1:1.
[0072] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A PEEK intervertebral fusion cage with sequential dual-drug delivery, characterized in that: It includes a polyetheretherketone carrier, a slow-release middle layer and an outer layer arranged from inside to outside; The surface of the polyetheretherketone carrier is pretreated to form a three-dimensional porous network structure; The sustained-release intermediate layer comprises sodium alendronate and dopamine, and sodium alendronate is synergistically coated on the surface of the polyetheretherketone carrier through self-polymerization of dopamine to form a sustained-release intermediate layer; The outer layer comprises a gel layer loaded with bone morphogenetic protein, hyaluronic acid forms a gel layer on the surface of the sustained-release intermediate layer through a cross-linking reaction, and the surface of the gel layer is loaded with bone morphogenetic protein to achieve sequential delivery of bone morphogenetic protein and sodium alendronate.
2. A PEEK intervertebral fusion cage with dual-drug sequential delivery according to claim 1, characterized in that: The pore size of the three-dimensional porous network structure is 1 to 4 μm.
3. The method for preparing a PEEK intervertebral fusion cage with dual-drug sequential delivery according to any one of claims 1 to 2, comprising the following steps: 1) Pretreatment of polyetheretherketone carrier: The polyetheretherketone carrier with a three-dimensional porous network structure on the surface is obtained by sulfonation treatment of polyetheretherketone; 2) Construction of sustained-release intermediate layer: The alendronate sodium solution and the dopamine solution are mixed to obtain solution A; the polyetheretherketone carrier obtained in 1) is immersed in solution A and magnetically stirred overnight at 4° C. in the dark; then rinsed with deionized water to obtain an intervertebral fusion cage preparation covered with a sustained-release intermediate layer; 3) Construction of the outer layer: The intervertebral fusion device preparation obtained in 2) is placed in a sodium hyaluronate solution containing a cross-linking agent, and a gel layer is formed on the surface of the intervertebral fusion device preparation after reacting at 4°C for 8-12 hours, and the cross-linking agent residue is thoroughly rinsed off; after washing, the preparation is sterilized, and the polyetheretherketone carrier is immersed in a bone morphogenetic protein solution overnight under a sterile environment at room temperature, and the intervertebral fusion device is obtained after natural drying.
4. The method for preparing a PEEK intervertebral fusion cage with sequential dual-drug delivery according to claim 3, characterized in that: 3) The bone morphogenetic protein solution is a 25-50 μg / mL BMP-2 solution.
5. The method for preparing a PEEK intervertebral fusion cage with sequential dual-drug delivery according to claim 3, characterized in that: 2) The mass ratio of dopamine to alendronate sodium in solution A is 2:0.2-5.
0.
6. The method for preparing a PEEK intervertebral fusion cage with sequential dual-drug delivery according to claim 3, characterized in that: 3) The cross-linking agent is EDC / sNHS cross-linking agent, sNHS is N-hydroxysulfosuccinimide, the EDC concentration in the cross-linking agent is 10-100 mg / mL, and the sNHS concentration is 11 mg / mL.
7. The method for preparing a PEEK intervertebral fusion cage with sequential dual-drug delivery according to claim 3, characterized in that: 1) The sulfonation treatment includes: soaking the polyetheretherketone in concentrated sulfuric acid to obtain a sulfonated polyetheretherketone sample; the sulfonated polyetheretherketone sample is rinsed with deionized water, soaked in a sodium hydroxide solution for 5 minutes, ultrasonically washed with deionized water again, and naturally dried to obtain a polyetheretherketone carrier with a three-dimensional porous network structure on the surface.
8. The method for preparing a PEEK intervertebral fusion cage with sequential dual-drug delivery according to claim 3, characterized in that: 3) The sterilization treatment is ultraviolet sterilization or irradiation sterilization for not less than 1 hour.
9. The method for preparing a PEEK intervertebral fusion cage with sequential dual-drug delivery according to claim 3, characterized in that: 3) The sodium hyaluronate concentration in the sodium hyaluronate solution is 3 mg / mL.
10. Use of the PEEK intervertebral fusion cage with dual-drug sequential delivery according to any one of claims 1-2 in the preparation of bone implant materials.
Citation Information
Patent Citations
A novel drug-loadable 3D-printed polyetheretherketone implant and its preparation method
CN115382017B